A Brief Primer of Three Major Counseling Theories for Use by School-Based Personnel - Whitley, Samuel F. (Journal of the American Academy of Special Education Professionals, 2020)
Childhood psychopathology is a large and concerning problem within the school setting. High prevalence rates of childhood psychopathology and resulting poor student outcomes reiterates the need for school service personnel to possess a basic understanding of the major therapeutic approaches to mollifying the difficulties presented by students. Three of these approaches are psychoanalysis, person-centered, and cognitive-behavioral therapy. This article provides teachers and varied school personnel with a working understanding of the theoretical foundations of each these therapies, as well as how each of these approaches conceptualizes childhood mental health disorders. Further, personnel are provided with an introduction to simple methods of addressing student psychological distress derived from each of the theories. These methods of redress include fostering student-teacher attachment, providing students with unconditional positive regard, and challenging cognitive distortions.